Processing of an anglerfish somatostatin precursor to a hydroxylysine-containing somatostatin 28. - Spiess, J (1985)
A novel 28-residue somatostatin (SS) has been isolated from anglerfish pancreatic islets and characterized by complete Edman degradation, peptide mapping, and amino acid analysis. The primary structure of this anglerfish SS-28 (aSS-28) containing hydroxylysine (Hyl) was established to be H-Ser-Val-Asp-Ser-Thr-Asn-Asn-Leu-Pro-Pro-Arg-Glu-Arg-Lys-Ala-Gly-Cys- Lys-Asn-Phe-Tyr-Trp-Hyl-Gly-Phe-Thr-Ser-Cys-OH. This sequence (with the exception of hydroxylysine-23, which is replaced by lysine) is identical to the sequence of the COOH-terminal 28 residues of prepro-SS II predicted on the basis of cDNA analysis [Hobart, P., Crawford, R., Shen, L., Pictet, R. & Rutter, W. J. (1980) Nature (London) 288, 137-141]. This is the first instance in which hydroxylysine (to date characteristically observed in collagen or collagen-like structures) has been found in a potential regulatory peptide. Chromatographic characterization of peptides, radiolabeled in islet culture, revealed that aSS-28 contained 10-12% of the radioactivity incorporated into the 8000- to 1000-dalton SS-like polypeptides, whereas 88-90% of this radioactivity was detected in anglerfish SS-14. It appears probable that aSS-28 represents the predominant primary cleavage product derived from prepro-SS II by cleavage at the COOH-terminal side of a single arginine. Based on knowledge of the collagen biosynthesis, it is speculated that hydroxylation may take place as an early post-translational event.